Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Susan Bessinger, Sam Bessinger, Joan St. Louis, David St. Louis, Ester Fletcher, Norman Fletcher, Lucille Fanucchi, Edward Fanucchi